Reversal of Fortune for Political Incumbents : Evidence from Oil Shocks - Arezki, Rabah (World Bank, Washington, DC, 2020)
Using a new data set of 207 national elections across 50 democracies, this paper is the first to systematically examine the effects of oil price shocks on incumbents’ political fortunes in developed oil-importing countries. We find that oil price increases systematically lower the odds of reelection for incumbents and increase the likelihood of changes in the ideology of the incoming government. These shocks are found to operate through lowering consumption growth.